Grover's-like drug eruption in a patient with metastatic melanoma under ipilimumab therapy. Issue 1 (16th August 2016) - Koelzer, Viktor H.; Buser, Tobias; Willi, Niels; Rothschild, Sacha I.; Wicki, Andreas; Schiller, Peter; Cathomas, Gieri; Zippelius, Alfred; Mertz, Kirsten D.
Abstract : Background: Dermatologic toxicity is an important adverse effect of immune checkpoint inhibitors targeting cytotoxic T-lymphocyte-associated antigen 4 (CTLA-4) and programmed cell death 1 receptor (PD-1) or PD ligand 1 (PD-L1). Skin toxicity most commonly includes a maculopapular erythematous rash and pruritus. Rarely life threatening complications such as Steven's Johnson syndrome or toxic epidermal necrolysis may occur. Case presentation: Here we report the uncommon event of a drug-induced transient acantholytic dermatosis (Grover's disease) in a 73-year-old Caucasian male treated with ipilimumab for metastatic melanoma. Five weeks after initiation of therapy, the patient developed a widespread polymorphic papulovesicular dermatosis on the trunk and proximal extremities with intense pruritus. Skin biopsy showed acantholytic dyskeratosis with interface dermatitis consistent with a Grover's-like drug eruption. Conclusions: These findings should raise awareness for uncommon immune-related dermatological toxicities of immunomodulatory antibodies targeting the CTLA-4 signaling axis. We recommend biopsies of unexpected skin lesions to rapidly identify dermatological adverse events of immune checkpoint inhibitors.